Interaksi Syariah dan Adat dalam Naskah Lontara Sukkuna Wajo - Zubair Zubair (Buletin Al-Turas, 2012)
This essay aimes to desribe the manuscript of Lontara Sukkuna Wajo and reveal it's islamic law (Syariah) context related to traditional law f Wajo. The methode used is filology and history. Filology hels the writer to describethe manuscripts physically and it's text, while the history guides the writer to know the context related to Wajo kingdom's history and how islamic and tradisioanl law applicated. The results shows that LOntara Sukkuna Wajo is the most complete Wajo's, from 14 th to 20 th century. Morever, the intersection of Islam and the kingdom of Wajo had influenced the history of it. Since Islam entered Wajo in 1610, the arrival of Datu Sulaiman (Patimang) and Datu ri Bandang as the holder of islamic authorit, Wajo had accomodatedIslam Law in it's Constitutional.